2021
DOI: 10.1371/journal.pone.0252622
|View full text |Cite
|
Sign up to set email alerts
|

The effect of colour on reading performance in children, measured by a sensor hub: From the perspective of gender

Abstract: In recent decades reported findings regarding gender differences in reading achievement, cognitive abilities and maturation process in boys and girls are conflicting. As reading is one of the most important processes in the maturation of an individual, the aim of the study was to better understand gender differences between primary school students. The study evaluates differences in Heart Rate Variability (HRV), Electroencephalography (EEG), Electrodermal Activities (EDA) and eye movement of participants durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…These findings are supported by theories regarding the characteristics of learners since they prefer colorful material in video form to printed material especially if it is not colorful and only filled with text (Jakovljević et al, 2021;Stern-Ellran, Zilcha-Mano, Sebba, & Levit Binnun, 2016;Treiman, 2016). In addition, colorful media can also help young learners memorize better (Diachenko, Kalishchuk, Zhylin, Kyyko, & Volkova, 2022).…”
Section: Analyzesupporting
confidence: 59%
“…These findings are supported by theories regarding the characteristics of learners since they prefer colorful material in video form to printed material especially if it is not colorful and only filled with text (Jakovljević et al, 2021;Stern-Ellran, Zilcha-Mano, Sebba, & Levit Binnun, 2016;Treiman, 2016). In addition, colorful media can also help young learners memorize better (Diachenko, Kalishchuk, Zhylin, Kyyko, & Volkova, 2022).…”
Section: Analyzesupporting
confidence: 59%
“…The various intervention methods used to improve the literacy, cognitive function and reading ability of children with dyslexia include the use of colored backgrounds or layouts [ 16 , 17 ], multisensory and multimedia methods [ 51 ] and virtual reality [ 52 , 53 ]. The combination of cognitive functions, linguistic literacy deficits and self-esteem interventions is not provided in any study in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have examined some factors that can improve or worsen reading performance. Among these factors, Jakovljevic et al found that gender [ 16 ] and color modifications [ 17 ] in text background and overlay influence their reading, with turquoise background/overlays and yellow backgrounds improving their performance. Moreover, some authors [ 18 ] have described the emotional and motivational aspects that characterize a child with an SLD, stating that a child with an SLD often presents a more negative self-concept, lower self-esteem, is more anxious and feels less emotional support.…”
Section: Introductionmentioning
confidence: 99%
“…Eye movement analysis of texts that are colour coded shows that retention is better for colour coded texts than for conventional formats (Ozcelik, E. et al, 2009). With children, it was found that boys have shorter reading time with longer saccade durations and more saccades than girls when reading a text that has a coloured background (Jakovljević et al, 2021).…”
Section: Eye Movements and Eye Trackingmentioning
confidence: 99%